Inequality in South Sulawesi; An Estimation of Development Transformation - Ahmad Kafrawi Mahmud; Khairul Yusuf; Sitti Aisyah (EcceS (Economics, Social, and Development Studies), 2022)
This study was conducted to measure the impact of economic growth, human development index, agglomeration, unemployment rate, and local government spending on regional development disparities in South Sulawesi Province in 2014-2020. The novelty of this research is that it uses Panel Data Regression Analysis with the Random Effect Model (REM) approach and uses the Williamson Index to measure the level of disparity. Based on the results of panel data regression analysis using the REM approach, it shows that the variables of economic growth and local government spending have a negative and significant effect on disparities between regions, the human development index variable and the unemployment rate have no effect on disparities between regions, and agglomeration variables have a positive and positive effect. significant to the disparity between regions. Taken together, the variables of economic growth, human development index, agglomeration, unemployment rate and local government spending have an effect on disparities between districts/cities in South Sulawesi Province in 2014-2020. The implications of this research are, among others, to encourage development in South Sulawesi Province, it is necessary to improve the quality of human resources and the role of the government in developing the potential of each sector equally in order to reduce regional development disparities that occur.